2015
DOI: 10.1177/1591019915583119
|View full text |Cite
|
Sign up to set email alerts
|

Long-term occlusion results with SILK flow diversion in 28 aneurysms: Do recanalizations occur during follow-up?

Abstract: Background and purpose The purpose of this article is to report on the long-term success rates of Silk flow-diverter (FD) treatment in a multicenter prospective study for the treatment of complex aneurysms. Methods Between May 2008 and January 2011, all consecutive patients featuring complex intracranial aneurysms eligible for FD treatment with the Silk in three neurovascular centers were included. Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Recurrence of a totally occluded aneurysm after FDS is a rare but possible finding. 20 In our case, a lenticulostriate artery was running off the aneurysm, which could explain the recurrent filling, as suggested by Trivelato et al 21 …”
Section: Discussionsupporting
confidence: 67%
“…Recurrence of a totally occluded aneurysm after FDS is a rare but possible finding. 20 In our case, a lenticulostriate artery was running off the aneurysm, which could explain the recurrent filling, as suggested by Trivelato et al 21 …”
Section: Discussionsupporting
confidence: 67%
“…A flow-diverter is a highly braided stent aimed to recover a natural blood flow in the cerebral artery and initiate aneurysm thrombosis [11]. Since the appearance in clinical practice in 2007, flow-diverter stents became a useful tool for treating complex, wide-necked aneurysms, which could not be treated with traditional clinical methods such as coiling and clipping [12, 13]. Several multicenter long-term studies reported a high occlusion rate and low risk of complications during the follow-up, although for some specific cases, especially for giant fusiform aneurysms, the complication rate is much higher [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…In Mpotsaris et al [66] single center series of 25 patients with 28 IAs treated with SFD, the rate of complete occlusion and neck remnant was 59 and 29%, respectively. In subgroups analysis (SFD alone vs adjunctive coiling), the rate of recanalization was 23% in 13 IAs treated with SFD alone and no recanalization was observed in 15 IAs treated with SFD and coiling.…”
Section: Clinical Profile and Completed Studiesmentioning
confidence: 95%